Sistem Informasi Monitoring Pengairan Sawah Subak Berbasis WebGIS - I Gusti Agung Anom Semara Putra; Ni Made Ary Esta Dewi Wirastuti; Komang Oka Saputra (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2022)
Subak is a traditional organization owned by the Balinese people to manage rice field irrigation. In the process of irrigating the fields, subak administrators and farmers check the condition of the irrigation in the fields by directly coming to the location to check the condition of the water level in the fields, so it is time consuming and less efficient. The creation of a geographic information system is intended so that subak administrators and farmers know the water level of the fields and regulate irrigation without going to the fields. The geographic information system is built using the Laravel framework equipped with a map. The map was created with the Google Maps API with the aim of displaying the location of rice fields. The result of this research is a geographic information system that can monitor the height of rice fields and display data on a map. The information system can also receive sensor data and send configuration data to Antares. In black box testing, the information system has been running according to the functions and scenarios given. Based on the results of the System Usability Scale test, the application obtained a score of 76,125 which indicates the application is classified as good and can be accepted by the user.